Invasive Fungal Rhinosinusitis: A Brief Review - Sajad Majid Qazi; Aamir Yousuf; Sulmaz Reshi (Highlights on Medicine and Medical Science Vol. 5, 2021)
"Fungal rhinosinusitis" as term describes fungal infection of the nose and paranasal sinuses. Fungal rhinosinusitis encompasses a wide variety of fungal infections based on wide spectrum of immune and pathological responses, that range from merely irritating the sinuses (allergic fungal sinusitis) to rapidly fatal disease (invasive fungal rhinosinusitis). Likewise fungal sinusitis has been classified as noninvasive and invasive type based on their pathophysiology and presentation. Symptoms spectrum can vary from simple rhinosinusitis, while on other extreme in immunocompromised it can cause significant morbidity and mortality. So much has been discussed and published on classifications, terminology management with early clinical suspicion, diagnosis and timely intervention medically and surgically that has proved beneficial. Given the current Covid-19 scenario and association with fungal rhinosinusitis in clinical practice, we aim to review the classification and current management strategies based on up-to-date literature.